DEVELOPMENT AND EVALUATION OF ALCOHOL RESISTANT FORMULATION BY USING DIFFERENT POLYMERS TO AVOID DOSE DUMPING (Cuestiones de Fisioterapia, 2025)
The objective of the proposed research work is to develop a novel technology for alcohol resistant modifiedrelease (MR) formulation, to overcome the problems of fast dissolution of MR formulation when taken withalcohol. To maintain the desired retention time of MR formulation in body irrespective of in-take fluid withwhich drug is administered and implementation of full factorial design to optimize the formulation.Preformulation studies which include various identification tests like organoleptic properties,solubility analysis, melting point determination, Evaluation of different grades polymers like compatibilitystudies with the selected model drugs. Formulation design and optimization without impacting thetherapeutic efficacy of drug product.Dose dumping is a phenomenon of drug metabolism in which environmental factors can cause the prematureand exaggerated release of a drug. This can greatly increase the concentration of a drug in the body andthereby produce adverse effects or even drug-induced toxicity.